Reputation Management Of Indonesian National Police During The Presidential Election In 2019 - Frizki, Yulianti Nurnisya (2022)
Reputation is an essential assessment for every corporation, both private and government owned. However, studies and references regarding reputation management for government-owned corporations are still relatively minimal. This research examines reputation management by the Indonesian National Police (INP) during the 2019 presidential election. At that time, many internal and external factors could threaten the police's reputation. The purpose of this research is (1) to explain the public perception of Indonesian police reputation during the 2019 presidential election, (2) to describe the public assessment on the reputation management elements carried out by the Indonesian police during the 2019 Presidential Election, and (3) to determine how the reputation management accomplished by the INP during the election. This research was done by combining qualitative method through internal interview data collection techniques as the primary data and supported quantitatively with survey techniques as secondary data. This research confirms that the excellence theory cannot be appropriately implemented due to the police forces' unique corporate characters. However, the survey showed that the Indonesian National Police still had a respectable reputation throughout the 2019 presidential election because a reputation management strategy that focuses on elements of employee behavior is the main factor in determining public satisfaction and public trust.